Hubungan Antara Kekerasan Orangtua Dan Konsep Diri Dengan Perilaku Bullying Pada Siswa SLB E Di Surakarta - Mulyani, Mulyani; , Dr. Sri Lestari, M.Si; , Dr. Nanik Prihartanti, M.Si (2016)
The aims of this research is to know: (1) correlational between parental violence and self-concept on bullying behaviors of students SLB e;(2) effective contribution of parental violence and self-concept toward bullying behaviors of students SLB E; (3) level of parental violence, self-concept, and bullying behaviors of students SLB E. The subject of this research was the students of SLB E YayasanPembinaanAnakNakal (YPAN) BhinaPuteraand SLB E Prayuwana, consisting 60 students.The data was collected by using the level of parental violence, self-concept, and the level of bullying behaviors. The technique of analyze the data use regression two predictions. The result of the research shows that there was correlation significantly between parental violence and self-concept on bullying behaviors. It means that parental violence and self-concept has influence toward bullying behaviors simultaneously. There are significant possitive correlation between parental violence and bullying behaviors; and significant negative correlation between self-concept and bullying behaviors. Effective contribution of parental violence toward bullying behaviors was 38,2%, while effective contribution of self-concept toward bullying behaviors was 17,1%. Generaly, parental violence's subject of research was classified as medium, self-concept was classified as medium, while bullying behaviors are classified low. Keywords: self-concept, parental violence, bullying behviors, Students SLB E (Emotional Disturbance Students)